TINJAUAN YURIDIS TERHADAP PENERAPAN DEPONERING DIKAITKAN DENGAN ASAS EQUALITY BEFORE THE LAW DAN ASAS LEGALITAS - Khairunnisa Khairunnisa; Mexsasai Indra; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Waiver of criminal cases for the sake of public interest or can be referred to as “deponering” is the embodiment of the opportunistic principle that has been legitimized by the state through Article 35 letter c of Law No. 16 of 2004 concerning the Republic of Indonesia Attorney General's Office and Article 14 letter h of the Law Code. Criminal Procedure. In fact, what should be an important note for the government and law enforcement officials is that from the perspective of the general public who do not understand the law comprehensively.This type of research is normative juridical research. In this research, the researcher discusses the principles of law, namely the principle of equality before the law, namely equality before the law. Then also using the legality principle which is the principle that determines that no action is prohibited and punishable if it is determined in advance in legislation, known in Latin as Nullum Delictum Nulla Poena Sine Praevia Lege Poenali (no offense, no punishment without advance regulation).The conclusions that can be obtained from the research results are: First, there is no derivative regulation in interpreting the meaning of the